Competencies Needed by Agricultural Communication Graduates: An Industry Perspective - A Christian Morgan (Journal of Applied Communications, 2010)
Competencies needed by agricultural comunication graduates to meet industry needs are dynamic, with new technohnologies being integrated into the communication industry annually. Over the past 35 years, several studies have reviewed agricultural communication curriculum by inquiring of students, graduates, faculty, and industry to determine what coursework, competencies, and objectives should be included to prepare undergraduates. Yet, the literature recommends reviewing curriculum every 2 to 5 years. This Delphi study was conducted to determine what competencies are desired by industry for bachelor of science graduates so existing curricullm at [university name] could be revised. Thirty-seven participants from industry came to consensus on 85 statements. Statements were categorized using curriculum categories from Terry et al. (1995). The ten statements receiving the highest level of agreement were “Conduct activities in an ethical manner,” “Ability to meet deadlines,” “Dependability,” “Strong work ethic,” “Reliable,” “Organizational skills,” “Demonstrate professional/business etiquette in workplace,” “Ability to multi-task,” “ Time management skills,” and “Ability to be a productive member of a team.” This study sought to address a portion of Agricultural Communications National Research Priority Area 4: “What are the skills, competencies, and resources necessary to prepare professional agricultural communicators for success in various aspects of agricultural knowledge management.”
Keywords: agricultural communication; graduates; Competencies; skills; knowledge management; stakeholders